PENGARUH LAMA PENGASAPAN DAN PENYIMPANAN TERHADAP BERAT, KARAKTERISTIK KIMIA DAN TOTAL MIKROBA TELUR ITIK ASIN - Tiya, Adi; Kartikawati, Diah; Hermanu, Bambang (Universitas 17 Agustus 1945 Semarang, 2025)
One of the various salted egg products with smoking methods is smoked salted eggs which have a distinctive aroma and taste. This study aims to determine the effect of smoking and storage time and its interaction on smoked salted eggs with on physical and chemical properties, total microbes as well. This research is experimental by using ducks eggs and a mixture of coconut shells and fibers, and rice husks as smoke fuel. The experimental design used is Randomized Complete Block Design (RCBD) with a 3x5 factorial pattern. As the first factor (P) is the smoking time which consists of P0= 0 hours, P1= 12 hours, P2= 15 hours while the second factor (H) is the storage time which consists of H0= 0 days, H1=7 days, H2= 14 days, H3= 21 days, and H4= 28 days. The variables observed were egg weight, albumen and yolk pH, moisture content, protein, and total microbial colony of smoked salted eggs. The results of the study were that the smoking time of 15 hours resulted in the lowest weight of smoked salted eggs (56.13g), while the storage time decreased the pH of albumen. Smoked salted duck eggs have a moisture content of 58.435-67.149%. The length of smoking increases the protein level. Salted duck eggs with a smoking time of 15 hours have the highest protein content, which is 15.39%. however, the duration of smoking and storage did not affect the total microbes of smoked salted eggs and there was no interaction between the duration of smoking and the duration of storage on the physical, chemical and total microbial properties.